Manifesting Plural Futures: Resisting AI's Colonising Impulses Through Counter-Imaginaries - Dinika, Adio-Adet (Imaginations)

(untitled) (York University, 2026)
This manifesto argues that artificial intelligence operates as a neocolonial epistemic infrastructure, extracting value from Global South data workers while erasing their cultural knowledge. Grounded in ethnographic research across East and Southern Africa, it advances a tripartite praxis of counter-imagination: repair, refusal, and reworlding. Drawing on decolonial theory, feminist scholarship, and African philosophies, the manifesto challenges dominant visual-conceptual frameworks in AI and calls for community-led alternatives rooted in epistemic justice and technological sovereignty. It is a call to reclaim imagination as a liberation technology and to manifest plural technological futures from below.